URGENSI PENGEMBANGAN KURIKULUM PAI MELALUI PENDEKATAN INTEGRATIF-INTERKONEKTIF - Anwar Dhobith; Tasman Hamami (Raudhah - Proud To Be Professional, 2023)
Abstract Efforts in the development of the Islamic Religious Education curriculum continue to be made so that it is relevant to the times and is able to equip students in solving life's increasingly complex problems. The problems of human life need to be solved through cooperation because they are aware of each other's shortcomings, which is in line with the concept of integration-interconnection. The method used in this research is descriptive qualitative method with library research. The results of the data analysis show that the integrative-interconnective approach in the development of the PAI curriculum contains a process of uniting religious knowledge with other branches of knowledge which have been considered dichotomous by looking at the reality of the problem more comprehensively, so as to be able to understand plurality with various disciplines. The integration of religious education and general education in schools that implement this curriculum is able to guide the morals and morals of students and provide skills to students that are not offered in public schools.